PERENCANGAN DESAIN KEMASAN SANJAI COKLAT UNICORN1007 LUBUK BUAYA PADANG - Dwi Ridvan Saputra, Dr. Syafwandi, M.Sn., Dr. M. Nasrul Kamal, M.Sn. (Universitas Negeri Padang, 2017)
This research is based on the existence of phenomenon which shows the low development of small and medium industry become one of the backbone of national economic development. One of the household industries is Kripik Sanjai. As it is known, Alam Minangkabau presents a wide range of food taste images that are very feasible to be developed again to produce a new flavor. Sanjai chips that have been circulating in the market only has several variants of flavors including: the taste of balado and the original taste of sanjai itself. With a view of the opportunities, Sanjai Coklat Unicorn tries to bring out the latest flavor variant, so that the sanjai lovers can feel some taste variants that continue to innovate.This final work aims to produce an interesting design design Sanjai Coklat Unicorn packaging. The method used by the author is started from the method of data collection that is by the method of observation, interview, and study documentation. Then proceed with data analysis method by using SWOT analysis (Strength, Weakness, Opportunity, Treatment), and analyzing product and doing creative design. In designing this packaging design the author will display the results of the layout, typography, and colors of interest in accordance with Sanjai Coklat Unicorn products.The results of the draft state that Sanjai Chocolate food packaging is more interesting than ever and people can recognize the nagari children's creations. Based on this final work suggested to the public is expected to better appreciate the design, because the role of design is very important and influential in various areas of communication, especially in visual communication. For students are expected to appreciate the works of design either the work itself or the work of others, therefore the importance of the role of a design. And for the producers, the Sanjai Coklat unicorn food design can be used as well as possible, so that the expected goals or results can be achieved.Keywords: Packaging, Sanjai Chocolate Unicorn, Design